NUSAWIRU MANGROVE FOREST ECOTOURISM DEVELOPMENT THROUGH LOCAL COMMUNITY EMPOWERMENT - Mulyanie, Erni; Maryani, Enok; Ningrum, Epon (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2023)
Characteristics of the Batukaras Mangrove Forest as a potential ecotourism area in Pangandaran Regency. The Mangrove Forest Ecotourism Area, which is located in Sanghiangkalang Hamlet, Batukaras Village, Cijulang District, Pangandaran Regency, has the potential to be used as a tourist destination object. However, with the existing conditions and potential, the management of the area is still not optimal and has not yet developed. The purpose of this study is to identify the characteristics and potential of mangrove forests as ecotourism areas and their development by involving local communities. The method in this research is descriptive method with data collection techniques through field observations, interviews, documentation studies and literature studies. The stages in this study are 1) data inventory 2) data collection; 3) Data analysis and synthesis stage. The results of this study indicate the natural characteristics consisting of three types of mangroves and fauna as well as the characteristics of human cultivation in the form of mangrove seeds and have potential as ecotourism areas: natural panorama, socio-economic potential, interesting activities that can be carried out in the Batukaras Mangrove Forest Area. Keywords : Ecotourism, mangrove forest, community empowerment